Quantum Difference Langevin System with Nonlocal q-Derivative Conditions - Surang Sitho; Sorasak Laoprasittichok; Sotiris K. Ntouyas; Jessada Tariboon (International Journal of Mathematics and Mathematical Sciences)
We introduce a new class of boundary value problems for Langevin quantum difference systems. Some new existence and uniqueness results for coupled systems are obtained by using fixed point theorems. The existence and uniqueness of solutions are established by Banach’s contraction mapping principle, while the existence of solutions is derived by using Leray-Schauder’s alternative. The obtained results are well illustrated with the aid of examples.